Desenvolvimento de tecnologia assistiva: teclado braile de baixo custo - FREITAS, Luiz Pedro Santos de (Instituto Federal do Amapá, 2021)
Inclusion is a topic that is constantly growing in society, it is extremely important, although they are widely discussed today, there is still a great lack of research and investment in this area. The present work presents a proposal to develop an assistive technology (AT) aimed at people who are blind or have low vision. Such a project refers to a Braille keyboard similar to that used in Braille typewriters, but with a differentiated proposal, which is inclusion in the digital age, where it stops using only paper and starts using the knowledge that already has to type and perform other interactions on the computer. Visually impaired people already use computers and smartphones with the help of screen reader software, the purpose of this work is to add more accessibility. In addition, the prototype to be developed can be used in teaching and learning Braille writing in a practical way and reducing the impact because it does not use paper.